School Heads’ Level of Competence in the Implementation of Inclusive Education - Fabunan, Shirley H.; Cabal, Esmen M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assessed the competence of school heads in implementing inclusive education in the Schools Division of Zambales. Using a descriptive-survey research design, the study involved 32 school heads and 594 teachers from 13 districts. The competence of school heads was evaluated across five dimensions: instructional leadership, managerial leadership, strategic thinking and innovation, stakeholder engagement, and personal excellence. Data were collected through a structured questionnaire and analyzed using statistical tools such as mean, t-test, and ANOVA. The results revealed that school heads were highly competent in all dimensions, as perceived by both groups of respondents. Instructional leadership was characterized by effective collaboration with teachers, analysis of student work, and policy implementation promoting peace and diversity. Managerial leadership highlighted the establishment of systems for collaboration and alignment of staffing with school goals. Strategic thinking and innovation emphasized vision-setting, promoting creativity, and aligning school culture with educational objectives. Stakeholder engagement focused on fostering partnerships and building supportive networks, while personal excellence underscored traits such as resilience, accountability, and emotional intelligence. Despite the high competence ratings, challenges remain in translating inclusive education policies into practice and addressing resource limitations. Significant differences in the perceptions of teachers and school heads were noted, highlighting the need for enhanced communication and collaborative leadership. The study recommends continuous professional development, provision of resources, and strategies to foster resilience among school heads. Strengthening stakeholder engagement and data-driven decision-making are also essential to further improve the implementation of inclusive education and create equitable learning environments.